I-Wire Heart-on-a-Chip II: Biomechanical analysis of contractile, three-dimensional cardiomyocyte tissue constructs. (15th January 2017) - Schroer, Alison K.; Shotwell, Matthew S.; Sidorov, Veniamin Y.; Wikswo, John P.; Merryman, W. David
Graphical abstract: Abstract: This companion study presents the biomechanical analysis of the "I-Wire" platform using a modified Hill model of muscle mechanics that allows for further characterization of construct function and response to perturbation. The I-Wire engineered cardiac tissue construct (ECTC) is a novel experimental platform to investigate cardiac cell mechanics during auxotonic contraction. Whereas passive biomaterials often exhibit nonlinear and dissipative behavior, active tissue equivalents, such as ECTCs, also expend metabolic energy to perform mechanical work that presents additional challenges in quantifying their properties. The I-Wire model uses the passive mechanical response to increasing applied tension to measure the inherent stress and resistance to stretch of the construct before, during, and after treatments. Both blebbistatin and isoproterenol reduced prestress and construct stiffness; however, blebbistatin treatment abolished subsequent force-generating potential while isoproterenol enhanced this property. We demonstrate that the described model can replicate the response of these constructs to intrinsic changes in force-generating potential in response to both increasing frequency of stimulation and decreasing starting length. This analysis provides a useful mathematical model of the I-Wire platform, increases the number of parameters that can be derived from the device, and serves as a demonstration of quantitative characterization of nonlinear, active biomaterials. We anticipate that this quantitative analysis of I-Wire constructs will prove useful for qualifying patient-specific cardiomyocytes and fibroblasts prior to their utilization for cardiac regenerative medicine. Statement of Significance: Passive biomaterials may have non-linear elasticity and losses, but engineered muscle tissue also exhibits time- and force-dependent contractions. Historically, mathematical muscle models include series-elastic, parallel-elastic, contractile, and viscous elements. While hearts-on-a-chip can demonstrate in vitro the contractile properties of engineered cardiac constructs and their response to drugs, most of these use cellular monolayers that cannot be readily probed with controlled forces. The I-Wire platform described in the preceding paper by Sidorov et al. addresses these limitations with three-dimensional tissue constructs to which controlled forces can be applied. In this companion paper, we show how to characterize I-Wire constructs using a non-linear, active Hill model, which should be useful for qualifying cells prior to their use in cardiac regenerative medicine.